2017
DOI: 10.1007/s10661-017-6427-z
|View full text |Cite
|
Sign up to set email alerts
|

Use of zeolite to neutralise nickel in a soil environment

Abstract: Nickel is a heavy metal which is a stable soil pollutant which is difficult to remediate. An attempt to reduce its impact on the environment can be made by changing its solubility. The right level of hydrogen ions and the content of mineral and organic colloids are crucial in this regard. Therefore, methods to neutralise heavy metals in soil are sought. There are no reports in the literature on the possibility of using minerals in the detoxication of a soil environment contaminated with metals. It is important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 26 publications
1
23
0
1
Order By: Relevance
“…Activity of the following soil enzymes was determined in soil samples after harvesting white mustard (day 40) and oats (day 80): The detailed procedures by which the activity of these enzymes is determined are described by Boros-Lajszner et al (2018).…”
Section: Methodology Of Determination Of the Soil Physical And Chemicmentioning
confidence: 99%
See 1 more Smart Citation
“…Activity of the following soil enzymes was determined in soil samples after harvesting white mustard (day 40) and oats (day 80): The detailed procedures by which the activity of these enzymes is determined are described by Boros-Lajszner et al (2018).…”
Section: Methodology Of Determination Of the Soil Physical And Chemicmentioning
confidence: 99%
“…& pH of the soil, total organic carbon, hydrolytic acidity, total exchangeable base cations, total cation exchange capacity of soil and soil saturation with base cations. The detailed procedures by which these determinations were made are described by Boros-Lajszner et al (2018). & Cadmium content in above-ground parts and roots was determined by atomic absorption spectroscopy (AAS) after microwave mineralisation as per the standard PN-EN 14084:2004 (N).…”
Section: Methodology Of Determination Of the Soil Physical And Chemicmentioning
confidence: 99%
“…Some literature data are not in accordance with the successful use of zeolite for the heavy-metal remediation of all types of polluted soil. Boros-Lajszner et al [105] reported that the addition of zeolites (clinoptilolite) determines the reduction of Ni accumulation in oats (11.69%) only grown in sandy silty loam, thus concluding that the efficiency of this mineral in nickel soil remediation is small. According to previous literature data [106], the authors attributed these results to the selectivity of clinoptilolite in absorbing heavy-metal ions (Pb > Cd > Cs > Cu(II) > Co(II) > Cr(III) > Zn >Ni(II) > Hg(II)).…”
Section: Natural Zeolites and Soil Pollutionmentioning
confidence: 99%
“…The concerned authorities have to take an active role to approve and license for an imported herbal medicine before it reaches the final customer. Contamination of herbs by toxic metals can be attributed to many causes including: environmental pollution, soil composition and using fertilizers [24,25]. Some of the metals such as Cu, Cd and Zn had a higher concentration than the allowable level, this can be attributed to the use of fertilizers & pesticides which contain these elements in their compositions [26,27].…”
Section: Elemental Quantitative Analysismentioning
confidence: 99%